The effect of template residual content on supercapacitive characteristics of Ni(OH)2, obtained by template homogeneous precipitation - Kovalenko, Vadym; Kotok, Valerii (Eastern-European Journal of Enterprise Technologies, 2019)
Nickel hydroxide is widely used in hybrid supercapacitors. High electrochemical activity is demonstrated by α-Ni(OH)2 prepared by template homogeneous precipitation. A possible disadvantage of template synthesis is the inclusion of template into nickel hydroxide and the lack of data on its residual content. Multiple rinsing method was proposed for lowering the content of template residue. The comparative study was conducted for the influence of residual template content and its use without the introduction of external binders. To conduct the study, samples of Ni(OH)2 were prepared by template homogeneous precipitation using ether cellulose template Culminal C8465 with a concentration of 0.5 %. The structural properties of the sample were studied by means of X-ray diffraction analysis and sample morphology – by means of scanning electron microscopy. Electrochemical characteristics were studied by means of galvanostatic charge-discharge cycling of pasted electrode prepared without and with 3 % of the binder in the supercapacitor regime. It was found that with the use of an external binder, the specific capacity of the sample with a high content of template residue is very low because of blocked active surface. When this sample was used without the introduction of an external binder, the specific capacity increases by 1.8–18.4 times. The decrease in the content of template residue due to one-stage rinsing improved the specific capacity of the samples insignificantly. It was found that two- and three-stage rinsing is optimal, in which the specific capacities of the samples improved by 4.3–53.9 times, to 490 F/g and 50.7 mA·h/g. The higher number of rinsing stages (lower content of template residue) results in a decrease of specific characteristics. It is possible that there is an optimal template content, at which the negative effect of the template is balanced with blocking the active surface and the positive effect – with stabilizing the nano-sized hydroxide particles. It is recommended to experimentally establish the optimal number of rinsing stages to form the optimal content of template residue for a specific template